Access to Soft-Surface, Green Exercise Trails in Mountainous, Urban Municipalities. (March 2019) - Chaney, Robert A; Stones, Elizabeth J
Soft-surface exercise infrastructure (ie off-road, mountain, and dirt trails) has been a particularly valuable community asset in mountainous, urban municipalities. This off-road, trail infrastructure can encourage individuals to engage in green exercise (ie physical activity done outside while in nature, for example, mountainous trails and near waterways). Green exercise can be helpful for encouraging individuals to participate in exercise who otherwise may not; it is especially helpful for promoting mental well-being and a sense of being connected to the environment. This study characterizes trail access and predictors among urban, mountainous municipalities in the Utah Wasatch Front region. Access was determined using two-standard deviation ellipses (2SDE) activity space analysis, and predictors were identified using multiple linear regression. About 42% municipalities had no trailhead access (ie no trailhead within its corresponding activity space). Trail density and trailheads were significantly correlated ( r  = 0.49, P  = .004). There was a significant trail density cluster in the southern area of the study region, centered all over the city of Alpine. Reduced-model regression yielded trailheads and home income as being significant predictors of trail density, and trail density and elevation as being significant predictors for trailheads. Results demonstrate patterns of access to green exercise trails that align with socioeconomic and municipal elevation. The results of this research should be insightful for those who work in exercise promotion and urban planners.